KEKUATAN PEMBUKTIAN SAKSI MAHKOTA PADA PERKARA PEMUFAKATAN JAHAT DALAM TINDAK PIDANA NARKOTIKA - Imra Leriwahyuli (Programa Magister Ilmu Hukum Universitas Ekasakti, 2021)
The Evidence Power of Crown Witnesses in Decision Number 400/Pid Sus/2019/PN.Pdg With 401/Pid Sus/2019/PN.Pdg And Decision Number 09/Pid Sus/2019/Pn.Pdg With 10/Pid Sus/2019/PN .Pdg is the same as other witnesses if they have met the requirements as witnesses. The crown witness in the narcotics crime case is the main witness to reveal the crime. The use of crown witnesses is very important because in this criminal act it is very difficult to find witnesses who can explain the chronology of a case because there are no victims and more than one perpetrator. The application of the Penalty in the Decision is a violation of Article 114 of the Narcotics Law. both defendants were guilty of violating Article 114 paragraph (1) of Law Jo, Article 132 paragraph (1) of Law no. 35 of 2009 concerning Narcotics. The judge handed down the same sentence.